Aṡar Istikhdām al-Qiṣṣah al-Muṣawwarah Bi aṭ-Ṭarīqah al-Mubāsyirah Fī Tanmiyah at-Ta`bīr asy-Syafawī Laday Ṭalabah aṣ-Ṣaff al-Awwal aṡ-Ṡānawi (Dirāsah Tajrībiyyah Bi Madrasah Insān Quranī, Aneuk Batee) - Ziyaush Shabri; Nur Chalis (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2021)
The Students of Modern Islamic Boarding Schools are distinguished in learning a variety of languages, one of which is Arabic. The teacher's method in Arabic learning is by using the audiolingual method. This method mostly involves memorizing vocabulary and Arabic grammar. However, the educators mostly use dialogue methods in teaching, of course; this process will be a good attempt to improve the ability of students to chat in Arabic. But in fact, many students are weak and unable to match the vocabulary and Arabic grammar that have memorized in the conversation. Therefore, the researcher examined the topic